2002
DOI: 10.1021/bi015959t
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Spontaneous DNA−DNA Interaction of Homologous Linear Duplexes

Abstract: Previously, we demonstrated the interaction of homologous linear duplexes with formation of four-way DNA structures on the model of five PCR products. We propose that homologous duplex interaction is initiated by the nucleation of several dissociated base pairs of the complementary ends of two fragments with Holliday junction formation, in which cross point migration occurs via spooling of DNA strands from one duplex to the other one, finally resulting in complete resolution into new or previously existing dup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Although we avoid making any conclusions about the mechanism of ELIC, it has been shown that double stranded homologous areas at the ends of two DNA molecules can form four-way DNA structures through strand exchange [17,18]. If recombination takes place at both insert fragment ends, bacteria might be able to take up the circular form, which resembles a replication This might indicate that the two fragments have annealed via one of their homologous ends, while the double annealed circular form is probably present in too low quantities to be seen.…”
Section: Vector and Insert Seem To Interact Already In Vitromentioning
confidence: 99%
“…Although we avoid making any conclusions about the mechanism of ELIC, it has been shown that double stranded homologous areas at the ends of two DNA molecules can form four-way DNA structures through strand exchange [17,18]. If recombination takes place at both insert fragment ends, bacteria might be able to take up the circular form, which resembles a replication This might indicate that the two fragments have annealed via one of their homologous ends, while the double annealed circular form is probably present in too low quantities to be seen.…”
Section: Vector and Insert Seem To Interact Already In Vitromentioning
confidence: 99%
“…Under appropriate conditions these fragments can form different structures [1] which are obtained with low yields but are sufficiently stable to be studied. Some of these conformations are multistranded structures the conformation of which is not yet entirely clear [2-4], some of them being also formed with non-repetitive sequences [4-6]. Other alternative conformations of these fragments are double-stranded structures, called hcDNA, which are the object of the present paper.…”
Section: Introductionmentioning
confidence: 99%